Linden Street area, general view of a private residence, Brookline, Massachusetts, 5 of 13. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Linden Street area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Linden Street Area (2) Residence in area.; Binder Number 4. Pocket Number: 8.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.